Convergence of the Export Structure of Romania, Croatia, Serbia and Bosnia-Herzegovina to the Structure of Import Demand in Developed Countries - Nikolić, Goran (Panoeconomicus, 2011)
The similarity coefficients of the export structures of Romania, Croatia, Serbia and Bosnia-Herzegovina and the import structure of the EU and the U.S. have increased since 2000, but to date, they have not reached a critical turning point. This indicates that the qualities of exports from the observed transitional economies have not rapidly improved, and the export structure remains relatively unfavourable, particularly when compared to advanced transitional countries. The most important factors in the success of advanced transitional economies were: the inflow of foreign direct investment, imports of modern technology (and later, their own development), innovation, development of small and medium sized enterprises, foreign competition, the development of a market economy and macroeconomic stability. The export structures of Romania, Croatia, Serbia and Bosnia correlate with improvement in the process of transition in the observed countries. In 2009 Bosnia had the absolute lowest level of similarity coefficient among the studied countries, followed by Serbia, Romania and Croatia, which corresponds to the overall economic performance and foreign trade of the observed economies.Key words: Similarity coefficients, Export, Import, Transitional countries, Convergence, EU, U.S.JEL: F16, B41.